La dictadura cívico-militar uruguaya (1973-1985): la construcción de la noción de víctima y la figura del exiliado en el Uruguay post-dictatorial - Magdalena Schelotto (Nuevo mundo - Mundos Nuevos, 2015)
The Uruguayan dictatorship (1973-1985) forced nearly 380,000 people, almost 14% of the population, into exile. Exile began as something temporary in neighboring countries in order to continue the militancy against the regime. To be a militant presupposes that militancy does not make one become a victim. Torture, imprisonment or death was just a consequence of that struggle. During the toughest years of the dictatorial repression, exile stopped being temporary and became something more long lasting and in further away countries. Soon, the various militant organizations abroad realized that in order to denounce the Uruguayan situation in the face of international organizations they must modify their discourse. This was done by adopting the transnational language of Human Rights. Their discourse moved away from militant language and on to talking about victims and to stop treating the human consequences of repression as something normal.In a country where victims associations were not created until almost the end of the conflict, the diaspora discourse will resonate in the first claims by the Uruguayan society for the restoration of democracy. Through a reconstruction of the evolution of the discourse of different groups, we get closer to the way the in which the Uruguayan society constructs the concept of victim and what are its consequences under a state policy of silence.